Effect of once‐weekly dulaglutide versus insulin glargine in people with type 2 diabetes and different baseline glycaemic patterns: A post hoc analysis of the AWARD‐2 clinical trial. Issue 11 (16th August 2019) - Giorgino, Francesco; Yu, Maria; Haupt, Axel; Milicevic, Zvonko; García‐Pérez, Luis‐Emilio
Abstract: The long‐acting glucagon‐like peptide‐1 receptor agonist dulaglutide acts by stimulating insulin secretion and reducing glucagon levels in a glucose‐dependent manner both in the fasting and postprandial states, resulting in reductions of both fasting glucose (FG) and postprandial glucose (PPG). In contrast, the main mechanism of action of basal insulin is to reduce elevated FG by inhibiting hepatic glucose production. The aim of the present post hoc analysis of the phase 3 AWARD‐2 trial was to investigate whether specific baseline glycaemic patterns respond differentially to dulaglutide compared to insulin glargine (glargine). We categorized participants into four subgroups based on prespecified glucose thresholds and their baseline FG and daily 2‐hour mean PPG: low FG/low PPG; low FG/high PPG; high FG/low PPG; and high FG/high PPG. Changes in glycaemic measures in response to treatment with dulaglutide or glargine were evaluated in each subgroup. At 52 weeks, significant reductions from baseline in glycated haemoglobin (HbA1c) were observed in all subgroups with dulaglutide 1.5 mg and with glargine (all P < .05), except in patients with low FG/low PPG who received glargine. Greater HbA1c reductions were observed with dulaglutide 1.5 mg compared to glargine in all subgroups (all P ≤ .05), except in the low FG/high PPG subgroup.